1997
DOI: 10.1152/ajpcell.1997.272.6.c1899
|View full text |Cite
|
Sign up to set email alerts
|

Whole cell Cl- conductances in mouse choroid plexus epithelial cells do not require CFTR expression

Abstract: Whole cell patch-clamp studies were performed with tissue isolated from the cystic fibrosis (CF) transgenic Cftrm1cam mouse, to determine whether anion currents in choroid plexus epithelial cells require the expression of cystic fibrosis transmembrane conductance regulator (CFTR). Inclusion of 0.25 mM adenosine 3',5'-cyclic monophosphate (cAMP) and 375 nM protein kinase A (PKA) in the pipette solution caused a significant activation of a Cl(-)-selective, inward-rectifying conductance in cells from wild-type an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 11 publications
4
31
0
Order By: Relevance
“…Nonetheless, Cl − currents have been found in mouse choroid plexus epithelial cells that have many of the characteristics of ClC-2 but also display some differences, such as dependence on intracellular ATP [14]; in fact, it was found that those currents persisted in ClC-2 knockout mice, pointing to an unidentified channel with characteristics that overlap those of ClC-2 [30]. The lack of an antibody with convincing specificity for ClC-2 in fixed tissues [35] precluded localization of the protein to the apical or basolateral membrane in Reissner’s membrane, although the effective inhibition of the inward current by ClC-2 antibody supports a similar epitope on the underlying channel or an associated protein.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, Cl − currents have been found in mouse choroid plexus epithelial cells that have many of the characteristics of ClC-2 but also display some differences, such as dependence on intracellular ATP [14]; in fact, it was found that those currents persisted in ClC-2 knockout mice, pointing to an unidentified channel with characteristics that overlap those of ClC-2 [30]. The lack of an antibody with convincing specificity for ClC-2 in fixed tissues [35] precluded localization of the protein to the apical or basolateral membrane in Reissner’s membrane, although the effective inhibition of the inward current by ClC-2 antibody supports a similar epitope on the underlying channel or an associated protein.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ATP-binding cassette proteins such as CFTR and p-glycoprotein are known to regulate other Cl -channels [19]. This possibility remains to be investigated; however, the regulatory protein involved in the choroid plexus is unlikely to be CFTR, since the inward-rectifying Cl -conductance is not impaired in the choroid plexus of CF "knock-out" mice [13].…”
Section: Discussionmentioning
confidence: 99%
“…2.5 nS) observed in the presence of ATP[γ-S] and AMP-PNP are similar in size to the currents observed in the presence of phorbol esters or the residual currents not blocked by divalent cations. These currents may be carried by volume-sensitive Cl -channels which are also expressed in choroid plexus epithelial cells[12,13] …”
mentioning
confidence: 99%
“…Chloride transport into the CSF is regulated in part by an apically localized inward-rectifying chloride channel, which is activated by intracellular cyclic AMP (cAMP) signaling (Brown et al, 2004;Kibble et al, 1997). To investigate a possible mechanism leading to the elevated chloride level in mutant CSF, we measured the intracellular concentrations of cAMP in CP cells freshly isolated from 5-day-old mutant and wild-type mice.…”
Section: Tg737mentioning
confidence: 99%